MAP6 interacts with Tctex1 and Cav2.2/N‐type calcium channels to regulate calcium signalling in neurons. (22nd November 2017) - Brocard, Jacques; Dufour, Fabrice; Gory‐Fauré, Sylvie; Arnoult, Christophe; Bosc, Christophe; Denarier, Eric; Peris, Leticia; Saoudi, Yasmina; De Waard, Michel; Andrieux, Annie
Abstract: MAP6 proteins were first described as microtubule‐stabilizing agents, whose properties were thought to be essential for neuronal development and maintenance of complex neuronal networks. However, deletion of all MAP6 isoforms in MAP6 KO mice does not lead to dramatic morphological aberrations of the brain but rather to alterations in multiple neurotransmissions and severe behavioural impairments. A search for protein partners of MAP6 proteins identified Tctex1 – a dynein light chain with multiple non‐microtubule‐related functions. The involvement of Tctex1 in calcium signalling led to investigate it in MAP6 KO neurons. In this study, we show that functional Cav 2.2/N‐type calcium channels are deficient in MAP6 KO neurons, due to improper location. We also show that MAP6 proteins interact directly with both Tctex1 and the C‐terminus of Cav 2.2/N‐type calcium channels. A balance of these two interactions seems to be crucial for MAP6 to modulate calcium signalling in neurons. Abstract : In the present study, we demonstrate that MAP6 proteins interact with Tctex1 and Cav 2.2/N‐type calcium channel to regulate calcium channels activity in hippocampal neurons. While MAP6‐E or its N‐terminal mutant form (MAP6‐EΔ1) seem sufficient to address Cav 2.2 channels properly, mutating the RRRIR motif to AAAIA in addition to deleting its microtubule‐binding motif Mn3 seem to prevent this activity (MAP6‐E ΔMn3AAAIA and MAP6‐EΔ1ΔMn3AAAIA mutants).